SAT-ESPEC: Analysis and Data Collection of Earth Station Transmission from a Satellite Network - Azevedo, Josinaldo; Barcellos, André L. C.; Mendes, Amanda C. A.; de Oliveira, Daniel; Vidal, Paulo C. S.; Bedo, Marcos (Proceedings of the Dataset Showcase Workshop (DSW), 2021)
Satellite networks are an essential component of Brazilian telecommunications infrastructure. In particular, satellites are the only network connection between several Brazilian remote locations and outposts. This study provides a sampled dataset, coined SAT-ESPEC, of spectrograms from five Brazilian stations. It includes real spectrograms collected from earth stations placed in the North of South America. Data were collected from an operating satellite by a Radiomonitoring and Geolocation Station from the Brazilian National Telecommunications Agency (ANATEL) at Rio de Janeiro city. The dataset fits the domains of radio propagation as well as network security and can be used for tasks such as classification, outlier detection, and time-series analyses.